Identifying patients with chronic lymphocytic leukemia without need of treatment: End of endless watch and wait?. (22nd January 2022) - Brieghel, Christian; Galle, Veerle; Agius, Rudi; da Cunha‐Bang, Caspar; Andersen, Michael A.; Vlummens, Philip; Mattsson, Mattias; Rosenquist, Richard; Smedby, Karin E.; Herling, Carmen D.; Bahlo, Jasmin; Hallek, Michael; et al.
Abstract: Introduction: Early‐stage chronic lymphocytic leukemia (CLL) challenges specialized management and follow‐up. Methods: We developed and validated a prognostic index to identify newly diagnosed patients without need of treatment (CLL‐WONT) by a training/validation approach using data on 4708 patients. Composite scores derived from weighted hazards by multivariable analysis defined CLL‐WONT risk groups. Results: Age (>65 years: 1 point), Binet stage (B: 2 points), lactate dehydrogenase (LDH) (>205 U/L: 1 point), absolute lymphocyte count (15–30 × 10 9 /L: 1 point; >30 × 10 9 /L; 2 points), β2‐microglobulin (>4 mg/L: 1 point), IGHV mutation status (unmutated: 1 point), and 11q or 17p deletion (1 point) were independently associated with shorter time to first treatment (TTFT). Low‐risk patients demonstrated 5‐year TTFT of 2% by internal validation, but 7–19% by external validation. Including all patients with complete scores, the 5‐year TTFT was 10% for the 756 (39%) CLL‐WONT low‐risk patients, and the 704 (37%) patients who were both CLL‐WONT and CLL‐IPI low risk demonstrated even lower 5‐year TTFT (8%). Conclusion: We have adopted the CLL‐WONT at an institution covering 1 800 000 individuals to allow patients with both low‐risk CLL‐WONT and CLL‐IPI to be managed by primary healthcare providers, thereby prioritizing specialized hematology services for patients in dire need.